2020
DOI: 10.1021/acsanm.0c01621
|View full text |Cite
|
Sign up to set email alerts
|

CoS2 with 3D Valence Electron Shell Structure for Pulsed Laser Application

Abstract: CoS 2 with a three-dimensional porous structure has attracted great interest because of its excellent electrical, magnetic, and optical properties. However, the nonlinear optical properties of CoS 2 have not been studied so far. Here, CoS 2 is utilized to act as an optical modulator first. A passively mode-locked Er-doped fiber laser is proposed with CoS 2 on a microfiber. The nonlinear optical properties of CoS 2 are systematically characterized. The modulation depth is 3.7% through a dual-balance monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…found that the nanowires improved the overpotential needed to reach a current density of 10 mA cm −2 by 45 mV. 1,21,22 This demonstrates the significance of design and engineering of catalyst structure not only to enhance the performance but also to reduce the cost by decreasing material usage. This is also the main motive behind the use of various micro-nanoporous, nanowire and nanotube structures for a wide range of applications.…”
Section: Introductionmentioning
confidence: 90%
“…found that the nanowires improved the overpotential needed to reach a current density of 10 mA cm −2 by 45 mV. 1,21,22 This demonstrates the significance of design and engineering of catalyst structure not only to enhance the performance but also to reduce the cost by decreasing material usage. This is also the main motive behind the use of various micro-nanoporous, nanowire and nanotube structures for a wide range of applications.…”
Section: Introductionmentioning
confidence: 90%
“…In past several years, novel nanomaterials have widely drawn much attention and interest due to their excellent mechanical, electronic and optical properties applied in a variety of fields, such as resonators, optical switching, optical modulators, and photodetectors. [ 1–5 ] Therefore, it is greatly significant to study the preparation of these materials and carry out the research on their characteristics. Although there have been multiple nanomaterials investigated, such as carbon nanotube, [ 6 ] graphene, [ 7 ] ferroferric‐oxide, [ 8 ] and zinc oxide, [ 9 ] it is only just beginning to explore the nonlinear optical properties and ultrafast photonics application of the novel nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, finding a natural graphene like 3D semiconductor material has become a new research hotspot. At this time, 3D semiconductor materials represented by MnO 2 [12] and CoS 2 [13] have entered the field of vision of researchers.…”
Section: Introductionmentioning
confidence: 99%